1995
DOI: 10.1148/radiology.195.1.7892448
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma in cirrhotic livers: detection with unenhanced and iron oxide-enhanced MR imaging.

Abstract: SPIO-enhanced MR imaging with proton-density-weighted or FLASH sequences was more accurate in the detection of small HCCs in cirrhotic livers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 0 publications
2
64
1
1
Order By: Relevance
“…Yamamoto's group reported that SPIOenhanced MR imaging with moderately T2-weighted or FLASH sequences was highly accurate for detecting small hepatocellular carcinomas in cirrhotic livers. 35 Our study revealed that pulse sequences with``halfway TEs'' were more sensitive in detecting damage of the liver parenchyma than heavily T1-or T2-weighted sequences. It may be argued that pulse sequences sensitive to liver parenchymal change and those sensitive to focal hepatic lesions are opposite sides of the same coin.…”
Section: Discussionmentioning
confidence: 65%
“…Yamamoto's group reported that SPIOenhanced MR imaging with moderately T2-weighted or FLASH sequences was highly accurate for detecting small hepatocellular carcinomas in cirrhotic livers. 35 Our study revealed that pulse sequences with``halfway TEs'' were more sensitive in detecting damage of the liver parenchyma than heavily T1-or T2-weighted sequences. It may be argued that pulse sequences sensitive to liver parenchymal change and those sensitive to focal hepatic lesions are opposite sides of the same coin.…”
Section: Discussionmentioning
confidence: 65%
“…11 SPIO acts as a negative contrast agent because uptake of its particles by KupŠer cells in the reticuloendothelial system of the liver 12,13 causes local magnetiĉ eld inhomogeneity and results in considerable T 2* shortening. 13 SPIO-enhanced MR is useful for detecting HCC [14][15][16] and has higher sensitivity than dynamic MDCT for detecting hypervascular HCCs smaller than 10 mm in diameter. 3 On dynamic MDCT, arterial parenchymal enhancement due to arterioportal venous (AP) shunt may become a false positive lesion in the investigation of HCC.…”
Section: Ct Versus Mr Imagingmentioning
confidence: 99%
“…Although most earlier clinical trials with magnetic nanoparticles as contrast agents were evaluated almost exclusively on T 2 -w fast spin echo (FSE) and T 2 *-w gradient echo (GRE) sequences, and the strong T 1 contrast enhancement effect of magnetic nanoparticles has rarely been used in clinical and molecular imaging (Reimer, 1995;Yamamoto, 1995;Tang, 1999), the effect of SPIO or USPIO on proton relaxation is not confined to T 2 and T 2 * effect. They should be considered to influence T 1 relaxivity with increased SI on T 1 -w GRE sequences at low concentrations.…”
Section: T 1 and T 2 (T 2 *) Multi-contrast For Cell Trackingmentioning
confidence: 99%